On-the-Go Training: Downloadable Modules to Train Medical Students to Care for Adult Female Sexual Assault Survivors - Molly Siegel; Estela Chen Gonzalez; Olindi Wijesekera; Katherine Finkelstein; Randi Petricone; Lois Glass; Annie Lewis-O'Connor; Conor Duffy; Nadia Quijije; Gail March; Shannon Bell (Association of American Medical Colleges, 2017)
Introduction Every medical provider encounters patients who have experienced sexual assault, and a patient's interaction with the medical system can impact long-term outcomes. Training to provide appropriate, compassionate care for this population is lacking in most medical school curricula. This educational resource contains three downloadable modules to train medical students in providing improved care for adult female survivors of sexual assault so students can feel more confident and empowered in caring for this population. Methods The modules are composed of an informational video on initial medical management, a patient interview simulation video, and a set of audio interviews on suggestions for practice. Interdisciplinary experts assisted in the modules' development. Associated materials include a 10 question pre- and posttest of medical knowledge, with additional survey questions to assess student attitudes and satisfaction outcomes. Results A cohort of 32 medical student volunteers from all class years tested the modules. Overall, student scores improved 20% (95% confidence interval, 16%-23%) from pre- to posttest. Students reported that their comfort in caring for an adult female sexual assault survivor increased after completion of the modules (p = .025). On the whole, students reported on the postsurvey that the modules enhanced their education, improved their comfort, and were appropriate for their level of education. Discussion These modules can enrich an undergraduate medical curriculum in a currently underaddressed topic, the care of female survivors of sexual assault. Empowering and educating students to care for this patient population can result in improved health outcomes.